2022
DOI: 10.1038/s41598-022-08673-4
|View full text |Cite
|
Sign up to set email alerts
|

Agrivoltaic systems have the potential to meet energy demands of electric vehicles in rural Oregon, US

Abstract: Electrification of the transportation industry is necessary; however, range anxiety has proven to be a major hindrance to individuals adopting electric vehicles (EVs). Agrivoltaic systems (AVS) can facilitate the transition to EVs by powering EV charging stations along major rural roadways, increasing their density and mitigating range anxiety. Here we conduct case study analyses of future EV power needs for Oregon, USA, and identify 174 kha of AVS viable agricultural land outside urban boundaries that is sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Solar energy might be a good option, and there are already many successful examples of greenhouse solar farms. The solar production system has been widely presented in a number of related studies [ 41 43 ]. It could be considered for integration into plant phenotyping platforms to achieve energy savings.…”
Section: Discussionmentioning
confidence: 99%
“…Solar energy might be a good option, and there are already many successful examples of greenhouse solar farms. The solar production system has been widely presented in a number of related studies [ 41 43 ]. It could be considered for integration into plant phenotyping platforms to achieve energy savings.…”
Section: Discussionmentioning
confidence: 99%
“…The APV is becoming popular in many countries, such as the USA, Japan, South Korea, China, France, and India [ 8 , 9 ]. For example, APV was found potential as electric vehicle charging station in rural Oregon, USA [ 10 ]. It was also reported that “ APV's dual function of agricultural yield protection while simultaneously generating solar power increases the economic output per area and enhances farmers' resilience against the impacts of global warming by securing and diversifying their sources of income ” [ 11 ].…”
Section: Introductionmentioning
confidence: 99%